Music attending to linear constituent structures in tonal music - Martínez, Isabel Cecilia (2018)
This article investigates the perception of constituent linear structures of tonal musical pieces, using a divided attention paradigm combined with a click-detection technique. Two experiments were run so as to test whether the boundary of a linear constituent appears as a focal point in the perception of musical structure. In Experiment 1, musicians and non- musicians listened to open foreground prolongations in phrases with clicks located at different points of their constituent structures. Significant differences in response times were found that depended on click position in relation to the boundary; participants were faster in detecting clicks at constituent boundaries, and slower for clicks located before boundaries, with no effect of rhythmic factors. Experiment 2 used the same experimental design to explore perception of open linear foreground prolongations, with the assumption that an effect of branching (left to right, or vice versa) could orient attention differently to the boundary region. Results were similar to those of Experiment 1. Overall, the evidence supports the idea that linear constituency is a significant feature of the perception of tonal musical structure. Dominant events become cognitive reference points to which the focus of attention is allocated, and subordinate, dependent events that are associated to the former, orient expectations of continuation and/or closure.